Edukasi Smart User dalam Memanfaatkan Media Sosial Pada Era Digital di SMKN 2 SAMPANG - Wahyu Liana; Faisol Faisol (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
This Community Service (PkM) aims to analyze smart users in using social media which is implemented in teaching and learning activities at Vocational High Schools, especially at State Vocational High School (SMKN) 2 Sampang. This emerged as a response to forms of learning that developed in the new era. The concept of implementing social media in learning is an effort to utilize social media as a tool in technology-based learning. The approach used in this research is qualitative with a case study type in order to explore the problem in depth and comprehensively capture the meaning of what occurs in the field. The PKM location is at SMKN 2 Sampang. Community service is carried out by smart users so that students can know that the benefits of digital are not only for personal interests, but can also be used for entrepreneurship.